Corrigendum - Agrivita Agrivita (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Corrigendum to “Effects of Foliar Application Chitosan and Salicylic Acid on Physiological Characteristics and Yield under Deficit Irrigation Condition” [AGRIVITA Journal of Agricultural Science, 43(1), 101-113]